Correction: Sodium doping for enhanced performance by highly efficient CsPbBr3 quantum dot-based electroluminescent light-emitting diodes. Issue 10 (2nd March 2022) - Huang, Yi; Tang, Pengfei; Zhang, Wenxia; Yan, Wensheng; Bin Liu,; Tang, Xiaosheng; Wang, Zhen; Peng, Yue; Chen, Weiwei
Abstract : Correction for 'Sodium doping for enhanced performance by highly efficient CsPbBr3 quantum dot-based electroluminescent light-emitting diodes' by Yi Huang et al., J. Mater. Chem. C, 2022, DOI: ; 10.1039/d1tc05997a .